Study on the mechanism of Gao-Liang-Huo decoction against dextran sulfate sodium-induced ulcerative colitis based on metabolomics and network pharmacology - Qiang Tian; Pei Hu; Miaohua Wang; Yu Hu; Like Xie; Zhixiong Li; Zhou Xu; Fang Liu; Chenggang Huang (Elsevier, 2023)
Backgrounds: Gao-Liang-Huo decoction (GLH), a traditional Chinese medicine consisting of gao liangjiang (the roots or tubers of Alpinia offinarum Hance) and guang huoxiang (the aerial parts of Pogostemon cablin (Blanco) Benth.), has been shown an effective therapeutic efficacy for ulcerative colitis (UC). However, the active compounds and underlying mechanisms involved in GLH treatment of UC remains unclear. This study aims to investigate the pharmacological mechanism of GLH on UC using an integrated strategy of metabolomics and network pharmacology. Methods: The experimental mice UC model was induced using dextran sulfate sodium (DSS). The disease activity index (DAI), colonic mucosa damage index (CMDI), biochemical assays, and histopathological analysis were used to evaluate the pharmacological effect of GLH. The LC/MS-based metabolomics was used for investigation of serum metabolites and metabolic pathways regulated by GLH. The potential targets and pathways of the active compounds in GLH were further explored using network pharmacology. Finally, the underlying mechanism of GLH on UC was verified by molecular docking and immunohistochemistry (IHC). Results: The pharmacological experiments showed that GLH significantly ameliorated the DAI, CMDI, MDA, MPO, and histopathological changes in DSS-induced UC. The 15 metabolites were identified by metabolomics, such as L-tryptophan, taurocholic acid, glycocholic acid, 3-indolebutyric acid, and tryptophol. These metabolites were found to be enriched in tryptophan metabolism, glycerophospholipid metabolism, and citrate cycle (TCA cycle). The results of network pharmacology revealed the key targets, such as PIK3CA, PIK3R1, JAK1, JAK2, and JAK3, mainly involved in the PI3K-AKT, JAK-STAT, and T-cell receptor signaling pathways. Molecular docking showed high affinity interaction of quercetin, isorhamnrtin, poriferast-5-en-3beta-ol, 1,7-diphenyl-5-hydroxy-3-heptanone, and medicarpin with PIK3CA, PIK3R1, JAK1, JAK2, and JAK3, respectively. Finally, the immunohistochemistry (IHC) results indicated that GLH regulated the PI3K-AKT pathway with decreased expression levels of PI3KCA and p-AKT in DSS-induced UC. Based on integration of pharmacological experiments, network pharmacology, and metabolomics suggested that GLH might improve DSS-induced US by modulating tryptophan metabolism, glycerophospholipid metabolism, PI3K-AKT, JAK-STAT, and T-cell receptor signaling pathways. Conclusions: This study highlights the potential of combining metabolomics and network pharmacology as a promising strategy for exploring the potential mechanism of TCMs.